Design thinking and creativity of colocated versus globally distributed software developers. Issue 5 (2nd September 2021) - Jolak, Rodi; Wortmann, Andreas; Liebel, Grischa; Umuhoza, Eric; Chaudron, Michel R. V.
Abstract: Designing software is an activity in which software developers think and make design decisions that shape the structure and behavior of software products. Designing software is one of the least understood software engineering activities. In a collaborative design setting, various types of distances can lead to challenges and effects that potentially affect how software is designed. To contribute to a better understanding of collaborative software design, we investigate how communication gaps caused by social and geographic distances affect its design thinking and the creativity of its discussions. To this end, we conducted a multiple‐case study exploring the design thinking and creativity of colocated and distributed software developers in a collaborative design setting. Compared with colocated developers, distributed developers spend less time on exploring the problem space, which could be related to different sociotechnical challenges, such as lack of awareness and common understanding. Distributed development does not seem to affect the creativity of their activities. Developers engaging in collaborative design need to be aware that problem space exploration is reduced in a distributed setting. Unless distributed teams take compensatory measures, this could adversely affect the development. Regarding the effect distance has on creativity, our results are inconclusive and further studies are needed. Abstract : The software design activities of six teams of developers (three colocated and three distributed) are observed and analyzed. Considering Design Thinking, more problem‐space exploration is observed in colocated teams. Furthermore, connection issues and lack of awareness are observed to be the main challenges to Design Thinking in the distributed teams. Considering Design Creativity, no difference is observed between colocated and distributed teams. Realizations occurred mainly during solution space exploration, and few divergent discussions are observed.